Generation of liquid crystallinity from a Td-symmetry central unit. Issue 28 (30th June 2016) - Sayed, Sayed Mir; Lin, Bao-Ping; Yang, Hong
Abstract : Liquid crystals containing an adamantane central unit with its four bridgehead positions partially or fully decorated with different numbers (1–4) of 3, 4, 5-tris(dodecyloxy)phenyl carbamoyl groups present diverse columnar phases (rectangular, square, and hexagonal). Abstract : A series of new columnar liquid crystals containing an adamantane central unit with its four bridgehead positions partially or fully decorated with different numbers (1–4) of 3, 4, 5-tris(dodecyloxy)phenyl carbamoyl groups were designed and investigated carefully to explore the structure–property correlations. The molecular structures and mesomorphic properties of the DLCs were characterized by 1 H-NMR, 13 C-NMR, IR, UV-vis, POM, DSC and XRD. It was found that the mesophase symmetry and thermal stability were extremely dependent on the structures of the adamantane derivatives. No mesophase was observed for the 1-adamantanecarboxylic acid derivativeADLC1, while two different mesophases were observed forADLC2, a 1, 3-disubstituted derivative functionalized with two 3, 4, 5-tris(dodecyloxy)phenyl carbamoyl groups at two symmetric bridgehead positions. At lower temperatureADLC2 exhibited a rectangular columnar phase, which switched to a square columnar phase possessing a wide temperature range. Similarly, a hexagonal columnar mesophase was observed for the bridgehead trisubstituted adamantane moleculeADLC3 . Interestingly, the fully bridgehead-functionalized 1, 3, 5, 7-tetrasubstituted adamantane compoundADLC4 completely lost liquid crystallinity.